Some Effects of endo-Brevicomin Background on Southern Pine Beetle (Coleoptera: Curculionidae: Scolytinae) Aggregation Behavior. Issue 6 (6th September 2021) - Sullivan, Brian T; Brownie, Cavell
Abstract: Semiochemical background in the environment can influence insect orientation to release points of the same or different semiochemicals. endo -Brevicomin is a pheromone component of the tree-killing bark beetle Dendroctonus frontalis Zimmermann (Coleoptera: Curculionidae: Scolytinae) that has a biphasic dose–response curve, enhancing attraction at low release rates but reducing attraction at high rates. We investigated the effect of artificial manipulation of background levels of endo -brevicomin on D. frontalis responses to sources of aggregation attractant in the field. Traps baited with the aggregation pheromone component frontalin and the host odor alpha -pinene were deployed either with or without a background of endo -brevicomin produced by three surrounding dispensers of this semiochemical each located 20 m away. Two tested levels of endo -brevicomin background caused catches to increase by an order of magnitude above those in the absence of background. Presence of background also altered the beetles' biphasic dose–response when endo -brevicomin dispensers were added to traps. Background reduced or concealed attraction-enhancement otherwise observed for low-release dispensers added to traps, and it decreased the release rate necessary to produce reductions in catches. We propose that spatial variability in abundance of natural, background sources of endo -brevicomin in the environment (i.e., infested trees) is a cause of the observed variability in effects of endo -brevicomin dispensers on southern pine beetle behavior in the field. Furthermore, our results illustrate the potential complexity of the density-dependent effects of biphasic pheromone components on bark beetle mass attack and colonization behavior.